Purification of an organic solvent-tolerant lipase from Aspergillus niger MYA 135 and its application in ester synthesis - Romero, Cintia Mariana (2012)
An organic solvent-tolerant lipase from olive oil-induced Aspergillus niger MYA 135 supernatant was purified using two methods: electroelution and ion-exchange chromatography. With electroelution purification was 8.4-fold and recovery 47% and with ion-exchange 16.6-fold and 53.4%, respectively. The purified enzyme showed a prominent single band with SDS-PAGE and was a monomeric protein of 68 kDa. The isoelectric point (pI) of the lipase was 5.1 and optimum pH and temperature for activity were 7.0 and 37 1C, respectively. The lipase showed affinity for esters with long acyl chains, with a Km of 0.99 mM for C18. Substrate specificity of the immobilized lipase was highest for C18 among the various a- and b-naphthyl esters assayed. Substrate specificity agreed with kinetics parameters of long-chain fatty acids (C18). Transesterification activity of the A. niger MYA 135 lipase indicates that it could be a potential biocatalyst for biodiesel production.